Exercise testing elite young athletes - Barker, A. R.; Armstrong, N. (The Elite young athlete, 2011)
Children and adolescents are becoming increasingly involved in competitive sport and, as a consequence, are engaging in specialized training with the objective of enhancing their sporting performance. An important aspect of achieving this goal is to ensure young athletes receive appropriate and on-going physiological assessment and support. Moreover, as young athletes require unique consideration (e.g. impact of biological maturity) compared to senior athletes, the challenge is for the exercise physiologist to adopt appropriate methods of assessment. This paper reviews field-and laboratory-based assessment of young athletes` aerobic fitness and performance during maximal intensity exercise. However, as studies of elite young athletes in their sporting environment are limited, the extant sport literature is complemented with data from untrained young people. The most appropriate variables to measure, which methodology and protocol to use, and how best to interpret the results of relevant tests are addressed. Key measurement issues relating to the specificity, validity and reliability of the physiological measures are examined and where possible, sport-specific measures are presented. The unique issues and considerations of providing continued physiological support to young athletes are discussed.